Strengthening High School Students’ Soft Skills through a Co-curricular Physics Program Integrated with Motorcycle Engineering and Business Competencies - Erlangga, Sy Dede; Budiarti, Lia Wahyuningsih; Sudiansyah, Sudiansyah; Silvianty, Alvionita; Safitri, Riski (FKIP - Universitas Riau, 2025)
The strengthening of science concepts in the Merdeka Curriculum requires a strong linkage between theoretical understanding and authentic application, particularly to develop soft skills relevant to the 21st-century workforce. However, physics learning in senior high schools still tends to emphasize cognitive aspects and provides limited practical exposure. This study aims to bridge this gap by integrating physics learning with competencies from the Motorcycle Engineering and Business (TBSM) program through a project-based co-curricular activity titled “Energy Efficiency and Workshop Service Innovation” at SMAN 2 Sandai. Employing a descriptive-qualitative method, data were collected through observation, semi-structured interviews, document analysis, triangulation, and member checking. The findings indicate differentiated soft-skill development among 26 participating students: three students reached Level 4, showing strong diagnostic abilities, data-based reasoning, scientific communication, and leadership; students at Level 3 demonstrated adequate mastery of concepts but inconsistencies in decision-making; while those at Levels 2–1 required further improvement in work discipline and entrepreneurial orientation. Overall, the study concludes that contextual project-based experiences effectively strengthen the connection between physics concepts and technical competencies while fostering students’ professional character development.